Analisis Risiko Bencana Kebakaran di Kecamatan Tambora Kota Administrasi Jakarta Barat - Nuniek Sutanti; Boedi Tjahjono; Lailan Syaufina (TATALOKA, 2020)
Tambora sub-district is a sub-district that has the smallest area in West Jakarta with the largest population, causing Tambora sub-district to be a densely populated area. Population density which is not matched by the carrying capacity of the environment causes a region to become slum and prone to fire disasters. This study aims to analyze the level of risk of fire disasters in Tambora Subdistrict, West Jakarta. The methodology used in this study were the Multi Criteria Evaluation (MCE) analysis and fire disaster risk analysis by considering the relationship between the hazard and vulnerability variables. The results of the fire disaster risk analysis showed that the most dominant level of fire risk was a moderate risk level of 65.7%, a high risk level of 27.8% and the smallest was a low risk level of 6.5%. Viewed from the size of the area included in the medium and high risk of fire, indicating that Tambora Subdistrict is a subdistrict prone to fire and has a large potential loss of both property and life.